Spatial subchannel allocation algorithm based on multiuser MIMO/OFDM systems - LU Xiao-feng; ZHU Guang-xi; WU Ren-yong; LIU Gan (Tongxin xuebao)
Spatial subchannels in multiuser multiple-input multiple-output/orthogonal frequency-division multiplexing （MIMO/OFDM） systems were invested. With the goal of maximizing overall data throughput the criteria of subcarrier allocation was derived and an adaptive spatial subchannel allocation algorithm was proposed. The simulation results show that the algorithm can achieve good performance and high total transmission rate efficiently.